PRESERVICE TEACHERS’ STRATEGIES TO NEGOTIATE ENGLISH TEACHING PRACTICES IN THE REMOTE AREA - Puspitasari, Febi; Nurkamto, Joko; Kristina, Diah (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2018)
Conditions and facilities of English language classes in the remote area encourage the negotiation of learning to solve problems. This narrative research aims to reveal strategies of pre-service teachers of the SM3T program in the process of the negotiation of English language learning. The study used diaries and interview transcripts from four teachers from Pidie Jaya and Sumba. The findings showthat teachers use interpersonal (IPS) and instructional (IS) strategies in the negotiation process. In Pidie Jaya, IPS strategies consist of the use of local languages and the help of local people. Meanwhile, IS strategies comprise learning groups and introduction to learning activities. In Sumba, teachers make language adjustment and establish rapport and informal communication as IPS strategies and they carry out buddy teaching and assign homework as IS strategies. This study contributes to the intercultural approach to designing English Language Education programs for remote areas. Keywords: EFL, remote areas, negotiation of learning STRATEGI GURU PRAJABATAN DALAM NEGOSIASI PEMBELAJARAN BAHASA INGGRIS DI DAERAH TERPENCIL Abstrak Kondisi dan fasilitas kelas Bahasa Inggris di daerah terpencil mendorong adanya negosiasi pembelajaran untuk menyelesaikan masalah. Penelitian naratif ini bertujuan untuk mengungkapkan strategi-strategi guru prajabatan program SM3T dalam proses negosiasi pembelajaran Bahasa Inggris. Studi ini menggunakan diary dan transkrip wawancara milik empat guru dari Pidie Jaya dan Sumba. Hasil penelitian menunjukkan bahwa guru menggunakan strategi Interpersonal (IPS) dan Instruksional (IS) dalam proses negosiasi. Di Pidie Jaya, IPS terdiri dari penggunaan bahasa lokal dan bantuan orang lokal. Sedangkan IS terdiri dari grup belajar dan pengenalan aktivitas-aktivitas pembelajaran. Di Sumba, guru melakukan penyesuaian bahasa dan membangun keakraban dan komunikasi informal sebagai IPS dan melakukan pengajaran dengan teman dan memberikan tugas rumah sebagai IS. Studi ini berkontribusi pada pendekatan antarkultur dalam merancang program Pendidikan Bahasa Inggris untuk daerah terpencil. Kata kunci: EFL, daerah terpencil, negosiasi pembelajaran